Outer actions of a discrete amenable group on approximately finite dimensional factors II, the III$_{λ}$-case, $λ eq 0$ - Katayama, Yoshikazu; Takesaki, Masamichi (Mathematica Scandinavica, 2007)
To study outer actions $α$ of a group $G$ on a factor $\mathcal M$ of type $III_λ$, $0